Design and Fabrication of a Semi- Automatic Shoe Polishing Machine for Small Scale Business - Taiwo Semiu Amosun; Shedrak E. Azike (Universitas Muhammadiyah Sidoarjo, 2022)
Shoe is generally made from leather which requires extreme care and regular polishing to maintain its shiny appearance. This work attempts to develop a semi-automatic shoe polishing machine for small scale enterprises. The machine is intended to grip the shoe at the right place, apply a layer of polishing wax all around the shoe and perform buffing action to obtain a shiny and assure minimum damage to the shoe. This semi-automatic shoe polishing machine is designed to consist of screw mechanism, a shaft, two bearings, two pulleys, belt, two fibred brushes, an electric motor and springs for gripping the shoe. The developed machine is limited to standard shoe sizes and capable of polishing a pair of shoes in 175 seconds.